2019
DOI: 10.3390/nu11122850
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study on the Combination Effect of Metformin and N-Acetyl Cysteine against Hyperglycaemia-Induced Cardiac Damage

Abstract: Chronic hyperglycaemia is a major risk factor for diabetes-induced cardiovascular dysfunction. In a hyperglycaemic state, excess production of reactive oxygen species (ROS), coupled with decreased levels of glutathione, contribute to increased lipid peroxidation and subsequent myocardial apoptosis. N-acetylcysteine (NAC) is a thiol-containing antioxidant known to protect against hyperglycaemic-induced oxidative stress by promoting the production of glutathione. While the role of NAC against oxidative stress-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…The precise mechanism of the NAC action is still unclear, but it is known that the development of inflammation during obesity induced by an HFD is associated with increased oxidative stress, which also worsens insulin signaling and accelerates myocardial damage. Thus, in our research, NAC probably resulted in reduced ROS generation that interfere with cellular processes, i.e., the degradation of membrane lipids (lipid peroxidation) and thereby increasing the metabolic activity of the tissue and reducing cellular apoptosis [36,37]. Similarly, we also observed that ALA reversed HFD-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The precise mechanism of the NAC action is still unclear, but it is known that the development of inflammation during obesity induced by an HFD is associated with increased oxidative stress, which also worsens insulin signaling and accelerates myocardial damage. Thus, in our research, NAC probably resulted in reduced ROS generation that interfere with cellular processes, i.e., the degradation of membrane lipids (lipid peroxidation) and thereby increasing the metabolic activity of the tissue and reducing cellular apoptosis [36,37]. Similarly, we also observed that ALA reversed HFD-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 66%
“…Rodrigues et al, in their study on obese mice, showed that NAC raised the protein level of phosphorylated Akt in the cardiac tissue, and thus the pAkt level was restored to values close to that of the control mice [36]. A study conducted by Johnson et al revealed that cardiomyocytes exposed to a high-glucose concentration with n-acetylcysteine showed improved glucose utilization caused by enhanced GLUT4 redistribution to the membrane allowing regulation and maintained proper glucose homeostasis [37]. In our study, we demonstrated that the dietinduced decrease in the heart pAkt(Ser473)/Akt ratio was completely reestablished.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15 Recent studies suggest that chronic hyperglycaemia is associated with ROS-induced oxidative stress, which in turn plays a crucial role in the development and progression of impaired cardiac function. 16 18 In a population-based study, cancer patients were found to have a higher risk of dying from cardiovascular disease and the risk is negatively related to the diagnosis at an early stage. 19…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers have begun to concern about drug combination treatment in diabetes (Johnson et al., 2019; Li & Zhang, 2016; Schlosser, 2019). Studies have shown that the components and contents of the biologically active compounds will change after combination, and the interactions between these compounds may make better therapeutic effects, with fewer side effects due to the decrease in dose of each drug (Cui et al., 2019).…”
Section: Discussionmentioning
confidence: 99%